2022
DOI: 10.7189/jogh.12.05034
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 in a primary school setting with and without public health measures using real-world contact data: A modelling study

Abstract: Background Stringent public health measures have been shown to influence the transmission of SARS-CoV-2 within school environments. We investigated the potential transmission of SARS-CoV-2 in a primary school setting with and without public health measures, using fine-grained physical positioning traces captured before the COVID-19 pandemic. Methods Approximately 172.63 million position data from 98 students and six teachers from an open-plan primary school were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Among these subjects, only one participant reported to be infected at school. Yan et al [ 46 ] demonstrated that, during the highly transmissible Omicron wave, risk of infection in teacher-to-teacher contact was higher compared to student-to-student or student-to/from-teacher contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these subjects, only one participant reported to be infected at school. Yan et al [ 46 ] demonstrated that, during the highly transmissible Omicron wave, risk of infection in teacher-to-teacher contact was higher compared to student-to-student or student-to/from-teacher contact.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience the school setting was characterised by a low risk for SARS-CoV-2 infection, since only one subject reported being infected at school. Several studies conducted in primary and secondary schools reported a low incidence of cases, monitoring both students and school personnel [ 17 , 46 , 48 , 49 ]. Macartney et al [ 50 ] observed few cases and secondary infection rates among pupils and school personnel in a population of 8.1 million Australians.…”
Section: Discussionmentioning
confidence: 99%
“…The same study concludes that uncontrolled transmission of SARS-CoV-2 in schools could spread transmission to other areas and increase the burden of contact tracing. In short, there is a growing body of literature and data (see also Yan et al 2022) showing that schools are a privileged environment for transmission and amplification of viral circulation, identifying schools as a major driver in the onward spread of infection. Therefore, it does not seem unreasonable that the mass of infections in September 2020 was strongly influenced by the reopening of schools.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are currently 13 SARS-CoV-2 variants in circulation, including Alpha, Beta, Delta, Gamma, and Omicron. Researchers have proven that the Delta and Omicron have increased infection rates and transmissibility [ 28 , 29 ]. Therefore, the one-off training method is not ideal for creating training and test sets for the COVID-19 infection simulation.…”
Section: Methodsmentioning
confidence: 99%